(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This literature review analyzes the impact of urban environmental factors on the development of lung cancer based on contemporary epidemiological and molecular-biological studies. Air pollution, particularly PM2.5, PM10, NO₂, traffic-related emissions, and industrial aerosols, was found to be closely associated with pulmonary carcinogenesis. Urbanization, the reduction of green areas, and climate change were identified as determinants increasing the risk of malignant respiratory pathologies. The findings demonstrate that strengthening environmental monitoring, optimizing urban planning, and developing air protection strategies constitute important directions in lung cancer prevention.